PENGARUH MUSIK INSTRUMENTAL ISLAMI TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS III PADA PELAJARAN MATEMATIKA DI SEKOLAH DASAR - Meta Siti Wulansari (COLLASE (Creative of Learning Students Elementary Education), 2019)
The use of Islamic instrumental music in mathematics learning especially to improve mathematical problem solving skills in elementary school students is the background of this research. This study aims to determine the influence of Islamic instrumental influence on mathematical problem solving abilities by using learning accompanied by Asian instrumental music. The research method used in this study was quasi-experimental. The population of this study was class III-B students as the experimental class and class III-C as the control class. The research instrument used in this study consisted of test and non-test instruments consisting of 5 items about mathematical problem-solving ability. From the results of research and data analysis that has been done, the results showed that there was a positive increase of 0.36 compared to the control class. The conclusion is that: (1) the achievement of mathematical problem solving abilities of students who use Islamic instrumental music is better than those who use Asian instrumental music; (2) learning by using Islamic instrumental music can be implemented according to the learning steps that have been prepared beforehand, so that students better understand the teaching material. Kata Kunci: Mathematical Problem Solving, Islamic Instrumental Music.